PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA DABITUKA TERHADAP KOLABORASI DAN PEMAHAMAN KONSEP SISWA KELAS IV SEKOLAH DASAR - Fenty Rakhmayanti; Kartika Yuni Purwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of the Problem Based Learning (PBL) model assisted by DABITUKA media on the collaboration and conceptual understanding of fourth-grade elementary school students. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research population consisted of all fourth-grade students at SDN Pringapus 01 and SDN Pringapus 02, totaling 67 students. The sample comprised 67 students, including 33 students in the experimental class at SDN Pringapus 01 and 34 students in the control class at SDN Pringapus 02. Data were collected through a conceptual understanding test and a collaboration questionnaire and were analyzed using the Independent Samples t-test and simple linear regression (ANOVA). The findings revealed a significant difference in conceptual understanding between the experimental and control groups, with a significance value of 0.008 (p < 0.05). The regression analysis also indicated that the PBL model assisted by DABITUKA media had a significant effect on students’ conceptual understanding, with a significance value of 0.018 (p < 0.05), contributing 16.8% to the improvement in conceptual understanding. Meanwhile, the regression analysis for the collaboration variable yielded a significance value of 0.813 (p > 0.05), indicating that the PBL model assisted by DABITUKA media did not have a statistically significant effect on students’ collaboration. Nevertheless, descriptive analysis showed that the average collaboration score of students in the experimental class was higher than that of the control class. Therefore, the PBL model assisted by DABITUKA media was effective in improving students’ conceptual understanding but did not demonstrate a statistically significant effect on students’ collaboration.